The Implementation of the Game Based Learning Model to Improve Student Learning Outcomes in Grade V at Inpres Rotnama Elementary School - Lowahna, Lusye; Ritiauw, Samuel Patra; Septory, Jekriel (Honoli of Journal Primary Teacher Education, 2025)
This study aims to analyze the implementation of the Game-Based Learning (GBL) model in improving the learning outcomes of fifth-grade students at SD Inpres Rotnama, Mdona Hyera District, Southwest Maluku Regency. This research employs the Classroom Action Research (CAR) method with 14 students (12 males and 2 females) as subjects. Data were collected through pre-test and post-test in Cycle I and Cycle II. The results of Cycle I showed an increase in the average score from 48.28 to 61.78, but it had not yet reached the Minimum Mastery Criterion (65). In Cycle II, the average score significantly increased to 78.21, indicating the successful implementation of GBL in improving student learning outcomes. Thus, the GBL model is effective in enhancing students' understanding and can be applied as an innovative learning method in elementary schools.